The Autonomous Learning Level of Speaking Skill in English Education Study Program - Ade Andriani, Fitri; Sujarwati, Iis (UIR Press, 2025)
This study aimed to assess the level of independent learning regarding speaking skills within the English Language Education Study Program. A quantitative descriptive design was utilized to analyze the speaking skill levels of students. A questionnaire consisting of 30 questions served as the instrument for this study. The researcher used likert scale in this research. The subjects included first-semester students from the English Language Education Study Program at the University of Bengkulu. The total population was comprised of 110 students, with 75 selected as research samples using a volunteer sampling technique, and participants volunteered for the study. The results revealed that the highest score was recorded for the statement,